1998
DOI: 10.1016/s0960-9822(98)70230-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal apoptosis induced by HIV-1 gp120 and the chemokine SDF-1α is mediated by the chemokine receptor CXCR4

Abstract: CXCR4, a seven transmembrane domain G-protein-coupled receptor for the Cys-X-Cys class of chemokines, is one of several chemokine receptors that can act as a co-receptor with CD4 for the human immunodeficiency virus (HIV-1) glycoprotein gp120 [1-3]. CXCR4 can mediate the entry of HIV-1 strains that specifically infect T cells, such as the IIB strain (see [4] for review). Recent reports indicate that gp120 can signal through CXCR4 [5] and it has been suggested that signal transduction, mediated by the viral env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
333
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(348 citation statements)
references
References 33 publications
13
333
2
Order By: Relevance
“…63 Binding of viral proteins (gp120) and SDF-1 to CXCR4 expressed on neurons could be a pathway for the neuronal apoptosis, suggesting an additional mechanism for neurodegeneration developed in HAD and HIVE. 63,64 These observations, taken together with those in this report, strongly support the idea that HAD is a metabolic encephalopathy fueled by viral replication and immune activation of macrophages and astrocytes. The heterogeneity in MP secretory functions and their interaction with other glial cells certainly play important roles in the pathogenesis of HAD and its associated encephalitis.…”
Section: Discussionsupporting
confidence: 84%
“…63 Binding of viral proteins (gp120) and SDF-1 to CXCR4 expressed on neurons could be a pathway for the neuronal apoptosis, suggesting an additional mechanism for neurodegeneration developed in HAD and HIVE. 63,64 These observations, taken together with those in this report, strongly support the idea that HAD is a metabolic encephalopathy fueled by viral replication and immune activation of macrophages and astrocytes. The heterogeneity in MP secretory functions and their interaction with other glial cells certainly play important roles in the pathogenesis of HAD and its associated encephalitis.…”
Section: Discussionsupporting
confidence: 84%
“…144 The HIV envelope protein has also been reported to cause apoptosis by binding to a chemokine coreceptor. [145][146][147][148] Several studies have indicated that macrophages are capable to trigger apoptosis of uninfected bystander CD4 þ and CD8 þ T cells. 149 Apoptosis involve the interaction between several death receptors (Fas, TNF-R, TRAIL-R) and their counterparts, their death ligands.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%
“…A number of viral and cellular factors produced by infected or activated cells over a long period of time appear to be responsible for the neuronal damage caused by HIV (recent reviews: Gartner and Liu, 2002;Gonzalez-Scarano and MartinGarcia, 2005;Jones and Power, 2006;Mattson et al, 2005). One of these factors is the HIV envelope protein gp120 that binds to chemokine receptors (i.e., CCR5 and CXCR4) on the surface of target cells, including neurons (Gartner and Liu, 2002;GonzalezScarano and Martin-Garcia, 2005;Hesselgesser et al, 1998;Jones and Power, 2006;Mattson et al, 2005). Several in vitro and in vivo studies have shown the neurotoxic potential of the envelope protein and the involvement of chemokine receptors in this process (Gartner and Liu, 2002;Gonzalez-Scarano and Martin-Garcia, 2005;Jones and Power, 2006;Mattson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of the co-receptors with the viral protein only partially resembles the interaction with their natural ligands , suggesting that activation of chemokine receptors may lead to cell death. Indeed, both apoptotic and pro-survival actions of chemokines have been reported (Cartier et al, 2005;Hesselgesser et al, 1998;Kaul and Lipton, 1999;Meucci et al, 1998). Thus, chemokine receptors may mediate both survival and apoptotic pathways in neurons.…”
Section: Introductionmentioning
confidence: 99%